Intensive and extensive margins of India's agricultural trade: implications for export diversification and development - Elumalai, Kanan; Kumar, Anjani (Emerald Publishing Limited, 2025)
This paper aims to analyze relative contribution of intensive margin (IM) and extensive margin (EM) to growth in India's agricultural exports for the period 2001 to 2020. It also analyses the determinants of IM and EMs through a standard gravity model.The study uses export data from United Nations Comtrade, which is accessed through World Integrated Trade Solution (WITS) software. Data for the period 2001 to 2020 were compiled for analysis using the Harmonized System (HS) of commodity classification system at the six-digit level. This study decomposed the contribution of IM and EM in the growth of Indian agricultural trade by using Hummels and Klenow's approach. After performing the export decomposition analysis, the authors analyze the factors influencing IM and EM by using the Tobit regression model and Poisson pseudo-maximum-likelihood (PPML) method of estimation.The EM grew at 1.24% per annum, while the intensive margin (IM) increased by 0.23%. The contribution of growth at the EM increased from 58.8% in 2001 to 70.2% in 2020. Export growth along the IM was relatively high for animal products and agricultural raw materials, while growth at the EM was an important contributor to the export growth of horticultural and processed agricultural products. There was a positive and significant effect of the free trade agreement (FTA) on export margins.More disaggregated commodity-specific studies on value chain analysis would provide valuable insights into the issues hindering exports and realizing the untapped export potential.There is a scarcity of holistic and recent studies illustrating the role of IM and EMs in agricultural trade growth, covering a large number of commodities and geographies associated with Indian agricultural trade. The study would be helpful to the stakeholders in facilitating informed policy decisions.